1981
DOI: 10.1001/jama.1981.03310430027015
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Manipulation for Low Back Pain

Abstract: A randomized clinical trial of rotational manipulation was conducted on 95 patients with low back pain selected for (1) the absence of any contraindications for vertebral manipulation, (2) the absence of any psychosocial problems that might affect the outcome of treatment, (3) the absence of any previous experience with manipulative therapy, and (4) the presence of palpatory cues indicating that manipulation might be successful. Patients were randomly assigned to one of two groups: an experimental group receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…In 4 trials, treatment duration was at the therapist's discretion, and details of treatment duration were not provided. [22][23][24][25][30][31][32][33][34] Eleven trials analyzed only the efficacy of high-velocity thrust manipulation techniques, 16,26,27,[30][31][32][35][36][37][38][39][40][41][42] 8 trials analyzed the efficacy of high-velocity thrust techniques in association with other techniques, 17,43-49 7 trials assessed a combination of high-velocity thrust manipulation and low-velocity mobilization techniques, [22][23][24][25]28,29,33,34,[50][51][52] and 1 trial compared different techniques of spinal manipulative therapy. 53…”
Section: Resultsmentioning
confidence: 99%
“…In 4 trials, treatment duration was at the therapist's discretion, and details of treatment duration were not provided. [22][23][24][25][30][31][32][33][34] Eleven trials analyzed only the efficacy of high-velocity thrust manipulation techniques, 16,26,27,[30][31][32][35][36][37][38][39][40][41][42] 8 trials analyzed the efficacy of high-velocity thrust techniques in association with other techniques, 17,43-49 7 trials assessed a combination of high-velocity thrust manipulation and low-velocity mobilization techniques, [22][23][24][25]28,29,33,34,[50][51][52] and 1 trial compared different techniques of spinal manipulative therapy. 53…”
Section: Resultsmentioning
confidence: 99%
“…Overall, seven studies known or purported to involve OMT for low back pain were reviewed and excluded for not meeting all eligibility criteria [34-40]. A subsequent source [41] indicated that an osteopathic manipulation technique was used in the Irvine study [42]. Although several of the six included OMT trials were identified in multiple bibliographic databases, five [42-46] were indexed in MEDLINE.…”
Section: Methodsmentioning
confidence: 99%
“…A subsequent source [41] indicated that an osteopathic manipulation technique was used in the Irvine study [42]. Although several of the six included OMT trials were identified in multiple bibliographic databases, five [42-46] were indexed in MEDLINE. The Cleary [47] trial was identified exclusively through the Cochrane Central Register of Controlled Trials.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 However, this finding is not universal. 18,19 Again, the study of van den Hoogen et al 12 may be helpful. Fig 5 is a plot of the results of that study showing the response rates of untreated patients with acute, subacute, and chronic low back pain.…”
Section: Discussionmentioning
confidence: 99%